PROGRAM PEMBENTUKAN MATRIX ADMITANSI PADA SISTEM TENAGA LISTRIK MENGGUNAKAN MATLAB - Widjaja, Maula Sukma (Jurnal Teknik Elektro, 2001)
The study aims to point out appluation of Matlab in analyzing admittance of electrical powersystem. Furthemore, its correlation with other pachage program such as MS Word or evenExcel, makes the analysis sampler and more flexible. Eventually the analysis made in Matlabformat, can be obtained or exported other related pachage program such as Excel and MSWord according to the fowsing NeedsKeywords: admittance, simulation, manipulation, arrays